Residues in the Polar Loop of Subunit c in Escherichia coli ATP Synthase Function in Gating Proton Transport to the Cytoplasm - Steed, P. Ryan (American Society for Biochemistry and Molecular Biology, 2014)
Rotary catalysis in F(1)F(0) ATP synthase is powered by proton translocation through the membrane-embedded F(0) sector. Proton binding and release occur in the middle of the membrane at Asp-61 on the second transmembrane helix (TMH) of subunit c, which folds in a hairpin-like structure with two TMHs. Previously, the aqueous accessibility of Cys substitutions in the transmembrane regions of subunit c was probed by testing the inhibitory effects of Ag(+) or Cd(2+) on function, which revealed extensive aqueous access in the region around Asp-61 and on the half of TMH2 extending to the cytoplasm. In the current study, we surveyed the Ag(+) and Cd(2+) sensitivity of Cys substitutions in the loop of the helical hairpin and used a variety of assays to categorize the mechanisms by which Ag(+) or Cd(2+) chelation with the Cys thiolates caused inhibition. We identified two distinct metal-sensitive regions in the cytoplasmic loop where function was inhibited by different mechanisms. Metal binding to Cys substitutions in the N-terminal half of the loop resulted in an uncoupling of F(1) from F(0) with release of F(1) from the membrane. In contrast, substitutions in the C-terminal half of the loop retained membrane-bound F(1) after metal treatment. In several of these cases, inhibition was shown to be due to blockage of passive H(+) translocation through F(0) as assayed with F(0) reconstituted into liposomes. The results suggest that the C-terminal domain of the cytoplasmic loop may function in gating H(+) translocation to the cytoplasm.